Colonel Muhammadin and Aman Nyerang’s Fight against the Dutch in Gayo Alas 1910-1950 - Dien Madjid; Azhar Saleh; Johan Wahyudhi (Buletin Al-Turas, 2022)
PurposeThe purpose of this study was to inform two warrior figures from Gayo, Colonel Muhammadin and Aman Nyerang who had not been recorded in the previously published historiography of the Aceh war. It was important regarding the dimension of the Aceh War which did not cover the coastal area, but also penetrated into Gayo and Alas Land.MethodThe researchers conducted several colonial data searches to find the war activities of Colonel Muhammadin and Aman Nyerang. Several annual reports of the colonial government, namely the Koloniaal Verslag and Dutch-language newspapers, were two important sources. The collected sources were then verified through external and internal criticism, until a selected source was found. The available data were then critically read and analyzed to obtain information to answer problems being investigated.Results/FindingsThe study found out that both figures used different war strategies against the colonials. Aman Nyerang was a fighter who liked guerrilla tactics and used close range attacks armed with a dagger or machete. Muhammadin was a warrior figure who adopted modern war strategies, because he had received Japanese military education. He used such strategies in ambushing the enemy, including by placing snipers in histroops.ConclusionColonel Muhammad and Aman Nyerang in the Gayo war had an important role in defending the Aceh region from Dutch rule. Therefore, the roles of both figures need to be recorded in the historiography using social history perspective to provide more comprehensive information for the next generation.